On the constitutive effects of contingent associations - Matthias Thiemann (Finance and Society, 2018)
Proposing a non-moralistic critique of the changes to neoliberal capitalism post-crisis, Konings provides a refreshing take on the dynamics of financial governance, emphasizing the way linkages between state and finance are structured by a speculative logic internal to neoliberalism. In this essay, I raise a number of questions about this characterization of neoliberalism, focusing on issues of agency and durability. First, does the turn to systems theory allow for a satisfactory account of the role that agency has played in the historical expansion of neoliberalism? And second, is it possible to envisage an end to neoliberalism when neoliberalism is so closely identified with capital dynamics in general?
Keywords: 300